Acinetobacter baumannii response to cefiderocol challenge in human urine - Nishimura, Brent (2022)
Cefiderocol (CFDC) is a novel chlorocatechol-substituted siderophore antibiotic approved to treatcomplicated urinary tract infections (cUTI) and hospital-acquired and ventilator-acquired pneumonia(HAP/VAP). Previous work determined that albumin-rich human fluids increase the minimuminhibitory concentration (MICs) of Acinetobacter baumannii against CFDC and reduce the expressionof genes related to iron uptake systems. This latter effect may contribute to the need for higherconcentrations of CFDC to inhibit growth. The presence of human urine (HU), which contains lowalbumin concentrations, did not modify MIC values of two carbapenem-resistant A. baumannii. Levelsof resistance to CFDC were not modified by HU in strain AMA40 but were reduced in strain AB5075.Expanding the studies to other carbapenem-resistant A. baumannii isolates showed that the presenceof HU resulted in unmodified or reduced MIC of CDFC values. The expression of piuA, pirA, bauA,and bfnH determined by qRT-PCR was enhanced in A. baumannii AMA40 and AB5075 by the presenceof HU in the culture medium. All four tested genes code for functions related to recognition andtransport of ferric-siderophore complexes. The effect of HU on expression of pbp1, pbp3, blaOXA-51-like, blaADC, and blaNDM-1, genes associated with resistance to β-lactams, as well as genes coding for efflux pumps and porins was variable, showing dependence with the strain analyzed. We conclude that the lack of significant concentrations of albumin and free iron in HU makes this fluid behave differently from others we tested. Unlike other albumin rich fluids, the presence of HU does not impact the antibacterial activity of CFDC when tested against A. baumannii.